Model of the trophic state of lagoons in high Andean zones of Peru, applying remote sensing and GIS - Guzman Vila, Vivian Anyela (2025)
The use of remote sensing is one of the most important tools for the evaluation of environmental problems, which are caused by humans or by natural activities and even driven by climate change. The objective of this research was to develop a model to determine the trophic state of lagoons in high Andean zones of Peru, based on remote sensing and GIS (Geographic information systems), in such a way that the estimation of the trophic state of these bodies of water can be determined without the need for a periodic or in situ sampling process. As a result, the model to determine the trophic state of the Paca and Ñahuimpuquio lagoon was obtained, it is TRIX = 5.943 - 0.000480B1 - 0.000695B2 + 0.00032B3 + 0.000811B4 - 0.000465B5, which is applicable to determine trophic state indexes during low levels, the model allows the elaboration of maps that facilitate the identification of zones with different eutrophication states, with the option of extracting for a given point the value of the evaluated parameter and its Cartesian coordinates. Finally, the proposed study can be adapted to other regions with similar characteristics; however, water quality monitoring data is required to validate a new model.